Trading in lives? : operations of the Jewish Relief and Rescue Committee in Budapest, 1944-1945 - Szita, Szabolcs (Central European University Press, 2005)
Set in the tumultuous moments of 1944-45 Budapest, this work discusses the operations of the Budapest Relief and Rescue Committee. Drawing out the contradictions and complexities of the mass deportations of Hungarian Jews during the final phase of World War II, Szita suggests that in the Hungarian context, a commerce in lives ensued, where prominent Zionists like Dr. Rezso Kasztner negotiated with the higher echelons of the SS, trying to garner the freedom of Hungarian Jews. Szita's portrait of the controversial Kasztner is a more sympathetic rendition of powerful Zionist leader who was later assassinated in Israel for his dealings with Nazi leaders. Szita reveals a story of interweaving personalities and conflicts during arguably the most tragic moment in European history. The author's extensive research is a tremendous contribution to a field of study that has been much ignored by scholarship--the Hungarian holocaust and the trade in human lives.